HUBUNGAN JUMLAH UANG SAKU DENGAN GAYA HIDUP HEDONIS MAHASISWA DI KOTA MADIUN - Novita Erliana Sari; Dwi Nila Andriani (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
His study aims to determine the relationship between the amount of pocket money and hedonic lifestyle in the city of Madiun. The sampling technique uses probability sampling. The number of samples in this study were 355 students. Research is a quantitative research developed with causality design where data analysis techniques use simple regression analysis. The results showed that there was a significant positive relationship between the amount of pocket money and the hedonic lifestyle of students taking study at Madiun City College. Keyword: Hedonic Lifestyle, Pocket Money